Japanese neonate with congenital chloride diarrhea caused by SLC26A3 mutation - Fuwa, Kazumasa; Hosono, Shigeharu; Nagano, Nobuhiko; Munakata, Shun; Fukamachi, Ritsuko; Okada, Tomoo; Takahashi, Shigeru; Takahashi, Shori; Sato, Naoyuki; Nakayama, Tomohiro (Pediatrics international, 2015)
Congenital chloride diarrhea (CCD) beginning in utero is a rare autosomal recessive inherited disorder characterized by impairment of Cl−/HCO3− exchange in an otherwise normal distal ileum and colon. Life‐long secretory diarrhea is caused by mutations in solute carrier family 26, member 3, (SLC26A3), which disrupt epithelial Cl−/HCO3− transport in the ileum and colon. Although 55 mutations in SLC26A3 have been identified throughout the world, few Japanese cases have been confirmed on genetic analysis. We report the successful treatment of a Japanese neonate with CCD caused by SLC26A3 mutation.